Improving Confidentiality, Integrity, Authenticity in Mobile Wallet - Agrawal, Garima; Sonker, Abhilash (International Journal of Computer Sciences and Engineering, 2025)
Mobile Transactions have seen an emerging trends after Demonetization and emergence of Digital–wallets. However, Transaction through mobile wallets or payment applications is not secure due to breaching of sensitive information by the attacker. When confidential data is breached all the sensitive information is lost. Hence, it is required to secure transaction by encryption. This paper shows the comparision in time performance of payment application using two Cryptographic Processes to enhance Confidentiality, integrity & Authenticity of private or confidential data. One Cryptographic Process includes combination of AES & ECC and Other Cryptographic process include RSA. In this paper, we have implemented using AES & ECC and compared the results with RSA